We Live Surrounded by Pigs: Naming the Space - Ungureanu, Dan (Linguistik Online, 2017)
The geographical nickname is a complex entity, both geographic, social and linguistic. The study is a sociolinguistic one. It focuses on the relation between language and space in Italy, Germany, Switzerland and Romania. We present the widespread practice of giving collective nicknames to the inhabitants of neighbouring villages or cities. This nicknaming reinforces the collective local identity, and defines narrowly the acceptable social and linguistic space. The individual and collective identity of the speakers is constructed through these nicknames. The local nicknames disappear in the 1950–1960, and are gradually replaced by other nicknames, encompassing larger geographical areas. These new nicknames reflect the new migrations.